Comparative Evaluation of Coronally Advanced Flap and Vestibular Incision Sub-Periosteal Tunnel Access Technique with Platelet-Rich Fibrin in the Treatment of Gingival Recession Defects- A Clinical Study - Nidhi Yadav; Manini Singh; Amit Wadhawan; Prashant Tyagi (Journal of Pharmacy and Bioallied Sciences)
Background and Aims: This study aim to treat gingival recession defects in the anterior and premolar teeth of the maxilla and mandible by comparing two methods: the coronally advanced flap (CAF) and the vestibular incision subperiosteal tunnel access (VISTA), both of which involve using platelet-rich fibrin (PRF). Materials and Methods: An age range of 18 to 50 years was examined for the study, which included twenty-four participants. The patients were chosen at random from the Outpatient Department of Periodontology at Shree Bankey Bihari Dental College and Research Centre in Masuri-Ghaziabad, U.P. They were divided into two groups of twelve each, and they were all diagnosed with isolated gingival recession defects on human maxillary and mandibular anterior teeth and premolars. Both Group A and Group B had recession defects covered with PRF membranes; however, Group A had a CAF and Group B underwent VISTA. Clinical parameters measured at baseline, 1-month, 3-months, and 6-months postoperative intervals included recession length, recession width, probing depth, width of keratinized tissue, clinical attachment level, and percentage of root coverage. Result: Both groups demonstrated notable enhancements in clinical parameters. However, the values of Group B were more statistically significant (P < 0.05) by showing a reduction in probing depth, recession length, recession width, clinical attachment level, and gain in width of keratinized tissue, as well as a percentage of root coverage, as compared to Group A. Conclusion: The VISTA technique was considered a more conservative approach for treating gingival recession defects with PRF membrane that showed good clinical outcomes and better results.